Kunkna Bhili Pictorial Glossary - Dhirubhai Patel; Bhagwandas Patel; Sonal Baxi (My University, 2008)
The words included in this glossary books are chosen on the basis of their picturability. These words consist of basic vocabulary items of the respective languages. These also include other frequent words which are used in day-to-day contexts in different walks of life.
Pictorial Glossary in Kunkna Bhili
Keywords: Kunkna Bhili; English; Gujarati